2016
DOI: 10.1152/ajpcell.00061.2016
|View full text |Cite
|
Sign up to set email alerts
|

Role of muscular eNOS in skeletal arteries: Endothelium-independent hypoxic vasoconstriction of the femoral artery is impaired in eNOS-deficient mice

Abstract: We previously reported that hypoxia augments α-adrenergic contraction (hypoxic vasoconstriction, HVC) of skeletal arteries in rats. The underlying mechanism may involve hypoxic inhibition of endothelial nitric oxide synthase (eNOS) expressed in skeletal arterial myocytes (16). To further explore the novel role of muscular eNOS in the skeletal artery, we compared HVC in femoral arteries (FAs) from eNOS knockout (KO) mice with that from wild-type (WT) and heterozygous (HZ) mice. Immunohistochemical assays reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Like in other mammalian conduit vessels, it responds to various contractile stimuli, i.e., α 1 ‐adrenoreceptor agonists, 5‐hydroxythryptamin, endothelin‐1, eicosanoids, NO inhibition, etc 4–8 . It is common knowledge that basal and agonist‐induced contractility of the FA could be altered by pathological conditions such as hypoxia, gram‐negative bacterial endotoxins, diabetes or microgravity 5,9–11 . Augmented vascular tone often coincides with advanced age, as at present, it is well appreciated that ageing increases muscle sympathetic nerve activity 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in other mammalian conduit vessels, it responds to various contractile stimuli, i.e., α 1 ‐adrenoreceptor agonists, 5‐hydroxythryptamin, endothelin‐1, eicosanoids, NO inhibition, etc 4–8 . It is common knowledge that basal and agonist‐induced contractility of the FA could be altered by pathological conditions such as hypoxia, gram‐negative bacterial endotoxins, diabetes or microgravity 5,9–11 . Augmented vascular tone often coincides with advanced age, as at present, it is well appreciated that ageing increases muscle sympathetic nerve activity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] It is common knowledge that basal and agonist-induced contractility of the FA could be altered by pathological conditions such as hypoxia, gram-negative bacterial endotoxins, diabetes or microgravity. 5,[9][10][11] Augmented vascular tone often coincides with advanced age, as at present, it is well appreciated that ageing increases muscle sympathetic nerve activity. 12 It has also recently been shown that on the level of smooth muscle cells, ageing induces a diminution of the Ca 2+ -dependent chloride conductance and a rise in agonistinduced contractility.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF could be positively regulated by HIF ‐ 1α and the expression of VEGF was higher in Tibetan pigs than that of Landrace pigs, which could promote endothelial cell proliferation and neovascularization, increasing vascular permeability to promote the development of cardiovascular system as a key vascular related factor (Srinivasan et al., 2015 ; Wang et al., 2020 ; Yu et al., 2018 ). The expression of eNOS and the relative vascular diameter were the highest in the high‐altitude Tibetan pigs, and it is believed that eNOS can regulate blood pressure and vascular permeability by influencing the vascular diameter (Janaszak‐Jasiecka et al., 2018 ; Kim et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of eNOS and the relative vascular diameter were the highest in the high-altitude Tibetan pigs, and it is believed that eNOS can regulate blood pressure and vascular permeability by influencing the vascular diameter (Janaszak-Jasiecka et al, 2018;Kim et al, 2016).…”
Section: Differential Expression Of Hypoxia-related Genes In the Heart And Their Associations With The Morphology And Physiology Of Pigsmentioning
confidence: 99%